The Reliability of Vibration based mobile phone in Detecting Peripheral Neuropathy in Patient with Diabetic Foot Ulcers - Jasmin, Muh; Yusuf, Saldy; Amrullah, Fitria; Arifuddin, Fitrawati (Persatuan Perawat Nasional Indonesia (PPNI) Jawa Tengah., 2021)
The aim of this study was to evaluate the reliability of mobile phone vibrations in detecting peripheral neuropathy in diabetic foot wound patients between the nurse and the patient's family. The design of this study was a pilot study with a cross sectional study approach. The study was conducted on 37 respondents in four wound care clinics in Makassar City and its surroundings. The instrument used is a mobile phone vibration using the vibrations-test application. Interater reliability analysis test used cohen's kappa test. The results showed that 67.6% of the patients did not feel the vibrations of the mobile phones performed by the nurses, while 70.3% of the patients did not feel the vibrations of the cellphones carried out by the family. Interrater reliability examination of diabetic feet using a mobile phone vibration shows an almost perfect agreement, namely (k = 0.973). The reliability of mobile phone vibrations using the vibrations-test application is quantitatively reliable. Thus, mobile phone vibrations can be used as an alternative screening tool to detect neuropathy in Diabetes Mellitus patients in the community.